Effect of year-round training on parameters of heart rate variability, central hemodynamics and physical working capacity in short-distance swimmers - Mykhaliuk, Ye. L.; Syvolap, V. V.; Horokhovskyi, Ye. Yu.; Potapenko, M. S.; Михалюк, Євген Леонідович; Сиволап, Віталій Вікторович; Гороховський, Є. Ю.; Потапенко, Марина Станіславівна; Михалюк, Е. Л.; Сыволап, В. В.; Гороховский, Е. Ю.; Потапенко, М. С. (Запорізький державний медичний університет, 2021)
Dynamic examination of athletes is of great interest for sports medicine specialists, as it allows measuring changes in athletes’ functional state in parallel with increasing athletic performance in a one-year training cycle. The aim of the work is to assess dynamic changes in parameters of heart rate variability, central hemodynamics and physical performance in short-distance swimmers during preparatory and competitive periods of the training process. Materials and methods. The swimmers (n = 94) qualified from the second-class sport qualification to Master of Sports of International Class were examined during the preparatory and competitive periods of the training process. Short ECG recordings of 5 minutes were used for the heart rate variability (HRV) analysis according to the International Standard. Results. In the preparatory period, the autonomic equilibrium index had a mean value of 3.104 ± 0.494 1/s2, and in the competitive period – 2.459 ± 0.248 1/s2 (P = 0.295). The initial distribution of athletes depending on the value of autonomic tone, according to the classification proposed by R. M. Bayevskiy, had the following ratio in the preparatory period: 75.0 % / 20.0 % / 5.0 %, vagotonic, normotonic and sympathotonic individuals, respectively, statistically significantly indicating the prevalence of athletes with vagotonia over normotonic individuals (P = 0.0005). In the competitive period, this ratio was 60.0 % / 40.0 % / 0 %. The central hemodynamic indices showed a downward trend as evidenced by a decrease in the cardiac index from 2.954 ± 0.126 l·min-1·m-2 to 2.862 ± 0.088 l·min-1·m-2 (Р = 0.510), although these values matched to the eukinetic circulatory type (CT) during both training periods. However, the ratio of hypokinetic, eukinetic and hyperkinetic CT in the preparatory period was 45.0 % / 45.0 % / 10 0 %, and in competitive period – 45.0 % / 55.0 % / 0 %, respectively. The mean value of physical working capacity (PWC170/kg) in the preparatory period was 15.54 ± 0.66 kgm·min-1·kg-1, and in the competitive period it was 18.09 ± 0.53 kgm·min-1·kg-1, making an increase of 16.41 % (Р = 0.0001). The functional state index (FSI) increased significantly by 25.08 % from 5.558 ± 0.322 r. u. to 6.952 ± 0.272 r. u. (Р = 0.00001). The correlation analysis during the preparatory period showed a significant positive correlation between Mo and PWC170/kg (r = 0.46, P = 0.040), ARI and CI (r = 0.50, P = 0.026), IARP and CI (r = 0.53, P = 0.017), stress-index and SI (r = 0.52, P = 0.019) and negative – between Mo and CI (r = -0.56, P = 0.009). In the competitive period, the general tendency of correlation interaction was remained, as evidenced by revealed positive relationships between Mo and FSI (r = 0.53, P = 0.017), ARI and SI (r = 0.51, P = 0.020). Conclusions. Short-distance swimmers in the competitive period had significantly higher level of physical working capacity (by 16.4 %), the functional state index (by 25.1 %), as well as parasympathetic tone of ANS in comparison with the preparatory period. The above-mentioned hemodynamic changes and autonomic balance indicators were associated with the increase in athletic performance: 4 (20 %) swimmers qualified for the title of Master of Sports of Ukraine, 2 (10 %) swimmers – for Candidate Master of Sports, and 2 (10 %) swimmers – for first-class sport qualification. Динамічне спостереження за спортсменами викликає чималий науковий інтерес для фахівців спортивної медицини, оскільки дає змогу констатувати зміни функціонального стану спортсменів паралельно зі зростанням спортивного результату протягом однорічного циклу тренувального процесу. Мета роботи – оцінити зміни параметрів варіабельності серцевого ритму (ВСР), центральної гемодинаміки та фізичної працездатності плавців на короткі дистанції в підготовчий і змагальний періоди тренувального процесу. Матеріали та методи. У підготовчому та змагальному періодах тренувального процесу обстежили плавців (n = 94) на короткі дистанції кваліфікації від майстра спорту міжнародного класу до спортсмена 2 розряду. Для аналізу ВСР використали короткі (5-хвилинні) записи ЕКГ відповідно до міжнародного стандарту. Результати. У підготовчому періоді 75,0 % плавців мали ознаки ваготонії, 20,0 % – нормотонії, 5,0 % – симпатикотонії. Різниця питомої ваги ваготоніків і нормотоніків вірогідна (p = 0,0005). У змагальний період відбувся зсув співвідношення вегетативного балансу в бік нормотонії: 60,0 % / 40,0 % / 0 % відповідно. Поділ плавців за типами кровообігу в підготовчому періоді: гіпокінетичний – 45,0 %, еукінетичний – 45,0 %, гіперкінетичний – 10,0 %; у змагальному періоді – 45,0 %, 55,0 %, 0 % відповідно. Середнє значення PWC170/кг зросло на 16,41 % (р = 0,0001). Індекс функціонального стану збільшився на 25,08 % (р = 0,00001). Кореляційний аналіз у підготовчий і змагальний періоди показав, що збільшення фізичної працездатності пов’язане зі збільшенням індексу Mo, зменшення індексу СІ – зі зменшенням ВПР і ПАПР і збільшенням Mo, а також зменшення СI – зі зниженням індексу стресу. Покращилися спортивні результати: 20 % (n = 4) плавців виконали норматив майстра спорту України, 10 % (n = 2) спортсменів стали кандидатами в майстри спорту, 10 % (n = 2) стали спортсменами 1 розряду. Висновки. Плавці на короткі дистанції у змагальний період мали на 25,1 % вищий рівень функціонального стану, на 16,4 % – фізичної працездатності, збільшення тонусу парасимпатичного відділу АНС порівняно з підготовчим періодом. У змагальному періоді збереглися кореляційні зв’язки, що виявлені в підготовчому періоді. Поліпшення спортивних результатів плавців на короткі дистанції асоціювалося з названими змінами показників гемодинаміки та вегетативного балансу. Динамическое наблюдение за спортсменами представляет большой интерес для специалистов спортивной медицины, поскольку позволяет констатировать изменения функционального состояния спортсменов параллельно с ростом спортивного результата в течение годичного цикла тренировочного процесса. Цель работы – оценить изменения параметров вариабельности сердечного ритма (ВСР), центральной гемодинамики и физической работоспособности пловцов на короткие дистанции в подготовительный и соревновательный периоды тренировочного процесса. Материалы и методы. В подготовительном и соревновательном периодах тренировочного процесса обследовали пловцов (n = 94) на короткие дистанции квалификации от мастера спорта международного класса до спортсмена 2 разряда. Для анализа ВСР использовали короткие (5-минутные) записи ЭКГ в соответствии с международным стандартом. Результаты. В подготовительном периоде 75,0 % пловцов имели признаки ваготонии, 20,0 % – нормотонии, 5,0 % – симпатикотонии. Разница удельного веса ваготоников и нормотоников достоверна (p = 0,0005). В соревновательный период произошло смещение соотношения вегетативного баланса в сторону нормотонии: 60,0 % / 40,0 % / 0 % соответственно. Распределение пловцов по типам кровообращения в подготовительном периоде: гипокинетический – 45,0 %, эукинетический – 45,0 %, гиперкинетический – 10,0 %; в соревновательном периоде – 45,0 %, 55,0 %, 0 % соответственно. Среднее значение PWC170/кг выросло на 16,41 % (р = 0,0001). Индекс функционального состояния увеличился на 25,08 % (р = 0,00001). Корреляционный анализ в подготовительный и соревновательный периоды показал, что увеличение физической работоспособности связано с увеличением индекса Mo, уменьшение индекса СИ – с уменьшением ВПР и ПАПР и увеличением Mo, а также уменьшение СИ – со снижением индекса стресса. Улучшились спортивные результаты: 20 % (n = 4) пловцов выполнили норматив мастера спорта Украины, 10 % (n = 2) спортсменов стали кандидатами в мастера спорта, 10 % (n = 2) стали спортсменами 1 разряда. Выводы. Пловцы на короткие дистанции в соревновательный период имели на 25,1 % выше уровень функционального состояния, на 16,4 % – физической работоспособности, увеличение тонуса парасимпатического отдела АНС по сравнению с подготовительным периодом. В соревновательном периоде сохранились корреляционные связи, которые проявлялись в подготовительном периоде. Улучшение спортивных результатов пловцов на короткие дистанции ассоциировалось с указанными изменениями показателей гемодинамики и вегетативного баланса.
Вплив цілорічного тренування на показники варіабельності серцевого ритму, центральної гемодинаміки та фізичної працездатності плавців на короткі дистанції
Влияние круглогодичной тренировки на показатели вариабельности сердечного ритма, центральной гемодинамики и физической работоспособности пловцов на короткие дистанции
Михалюк Є. Л. - ORCID ID: 0000-0003-3607-7619; Сиволап В. В. - ORCID ID: 0000-0001-9865-4325.
Keywords: short-distance swimmers; rank from firstclass athletes to master of sports of international class; heart rate variability; central hemodynamics; physical working capacity; periods of the training process; плавці на короткі дистанції; кваліфікаційний ранг від спортсмена 1 розряду до майстра спорту міжнародного класу; варіабельність серцевого ритму; центральна гемодинаміка; фізична працездатність; періоди тренувального процесу; пловцы на короткие дистанции; квалификационный ранг от спортсмена 1 разряда до мастера спорта международного класса; вариабельность сердечного ритма; центральная гемодинамика; физическая работоспособность; периоды тренировочного процесса